The Russian enterprise directors? Perceptions on the innovation activity of their company. A briefing of the empirical results - Alexey Prazdnichnykh; Kari Liuhto (Journal for East European Management Studies, 2010)
The main objective of the article is to analyse the current state of the innovation activity among the Russian enterprises. The empirical evidence shows only 13% of the sample indicated that innovation is the first priority for the firm. We propose that the Russian Government designs innovation policies which takes into account the differences between the industries. Secondly, the Russian Government should promote international innovation cooperation by setting up technology trade agents in the most active countries in terms of innovation cooperation, such as Germany, the USA, and Finland. Thirdly, the CEOs of the Russian enterprises consider R&D funding as well as policy steps to increase R&D effectiveness, as those measures of innovation policy which should be of the highest priority for the Russian government. – – Das Ziel dieses Artikels ist es, den aktuellen Stand der Innovationsaktivitäten von russischen Unternehmen zu analysieren. Die Ergebnisse zeigen, dass nur für 13% Innovation oberste Priorität hat. Wir schlagen vor, dass die russische Regierung eine Innovationspolitik entwickelt, welche die Unterschiede zwischen den Branchen berücksichtigt. Zweitens sollte die russische Regierung die internationale Zusammenarbeit in Bezug auf Innovation durch die Einrichtung von Technologietransfer mit den aktivsten Ländern wie Deutschland, den USA und Finnland fördern. Drittens erachten die russischen CEOs die Förderung von Forschungs- und Entwicklungsausgaben sowie entsprechende Richtlinien als jene politischen Maßnahmen die höchste Priorität genießen sollten.
Keywords: 650; innovation activity; Russia; Strategy; innovation policies Russian Government